Financial feasibility of a waste to energy facility: a case study. (20th April 2020) - Malwe, Aditya Atul; Hebbar, Sunith
The study focuses on analysing the financial feasibility of a waste-to-energy (WtE) plant that has been proposed in the Raipur City of India. The WtE system being highly complex with various subsystem it is critical to understand the interactions among these subsystem for effective decision making. System dynamics (SD) methodology is one of the modern and comprehensive methodologies adopted for this purpose. In this study a SD model has been developed for the WtE system and simulated for 20 years to check on the financial viability. The influence of tipping fee and electricity selling price on NPV was analysed as scenarios. Also, the capacity analysis was carried for the system. The results revealed that the plant is financially feasible with required return of 12% and 18% (positive NPVs). The capacity shortfall will incur by around 11 years from now. The consideration of dynamic behaviour in the results improves the effectiveness of strategic policies formulated by the decision makers. Appropriate suggestions were made based on these results.